PERAN KEPALA SEKOLAH DALAM MENINGKATKAN MINAT MEMBACA AL-QUR’AN DI MADRASAH IBTIDAIYAH RAUDLATUL ULUM PALAS, LAMPUNG SELATAN - Nurhakim, Nurhakim; Warisno, Andi; Murtafiah, Nurul Hidayati (STIT AL MULTAZAM, 2022)
The head of the Madrasah is the leader in his institution, namely moving, influencing, motivating, and directing his subordinates in the organization or educational institution to achieve predetermined goals. The purpose of this study was to examine how the leadership role of the madrasah head in developing an interest in reading the Qur'an, examine how the leadership style of the madrasah principal in developing an interest in reading the Qur'an and examine the supporting factors in developing an interest in reading the Qur'an in Madrasa Ibtidaiyah Raudlatul Ulum. The research method used in this study uses qualitative methods, with the type of phenomenological research, while using data through interviews, observation, and documentation. The results of the study show that the leadership role of the Madrasah Head in developing an interest in reading the Qur'an has an important role in improving the culture of reading the Qur'an, namely that the Head of the Madrasah must have the right strategy in collaborating and encouraging the involvement of all educators in developing an interest in reading. Al-Qur'an. The leadership style of the madrasa head in developing an interest in reading the Qur'an is applied through a democratic, participative, and motivational leadership style, while the supporting factors in developing an interest in reading the Qur'an are creating an environment that can increase interest in reading the Al-Qur'an.